REKAYASA BUDIDAYA KEPITING BAKAU MELALUI PEMOTONGAN KAKI JALAN DALAM UPAYA PENINGKATAN PRODUKSIKEPITING SOKA (SOFT SHELL) - Istiyanto Samidjan; Diana Rachmawati (LPPM Universitas Pekalongan, 2015)
This study aimed to determine the effect of cutting the foot of the survival, growth and the rate of mangrove crab molting, to know the cutting foot path can maintain the survival, growth and molting best for mud crab. This study used an experimental method with a completely randomized design (CRD) 6 treatments and 10 replications that treatment A (1 foot cutting path, B (cutting 2 feet or legs road), C (3 ft cutting path), D (cutting 4 feet or two pairs of feet road), E (cutting all roads feet), and F (without cutting the foot of the street). the material used were 120 mangrove crab tails with an average weight of 100 g / head. Case studies in the form of basket made of plastic sheeting with the size of 30x30x20 cm by 100 basketball. the data was taken from the data of survival, absolute growth, the daily growth. the data were analyzed variety, to determine differences among the treatments tested the effect of Dual Duncan area. While the water quality data, the rate of molting analyzed descriptively. The results showed that cutting the leg was highly significant (P <0.01) to the absolute growth and the daily growth, but significant (P <0.05) against survival rate and molting. The highest absolute growth value E (64.48 ± 28.41g), and the highest daily growth rate in treatment E (2:08 ± 0.79%). The highest survival value was treated F (90 ± 31.62%) and the highest molting in treatment E (80 ± 42.16%). Water quality media for research on decent range for maintenance of mud crab (Scylla paramamosain).Keywords : Mud crab, cutting the foot path, growth, survival, and molting